Análise de regiões em cenários agrícolas utilizando um sistema de visão catadióptrico - Rodrigues, Victor de Assis [UNESP] (2014)
Vision System is widely used in applications related to Precision Agriculture. The ability to extract large sets of data from the environment and its low acquisition costs makes them popular among different types of existing sensors. In some activities, becomes necessary to increase the field of view of the application to increase the knowledge about the environment. Omnidirectional Catadioptric System provide techniques to capture complete images of the environment using a combination of lenses and mirrors. This work aimed the application of a catadioptric system using hyperbolic mirror, to perform the survey information of agricultural natural scenery. The omnidirectional image is treated with techniques of image processing and rectified, creating a new panoramic image. Then, its quadrants are extracted, yielding four new images that represent the side view of the vehicle. A Step by color segmentation was proposed using as a basis the Otsu Threshold algorithm. Filters are applied to optimize the results. At the end of the process, it was possible to view the regions of interest in each quadrant